Investigation of Indoor Radiation Levels within Lead City University’s Academic Buildings - Ruth R. ADELAJA; Rhoda I. ADELAJA; Henry OTOBRISE; Adefope OWOJORI; Babatunde ADEBO (FUDMA Journal of Engineering and Technology, 2025)
A study was conducted at Lead City University to evaluate indoor gamma radiation exposure and its potential health implications. Measurements were taken using a Gamma Scout Geiger counter at walls, floors, and room centers across 10 aerated and non-aerated locations. In aerated areas, the average equivalent dose rate (EDR) ranged from 0.614 µSv/h (SB) to 2.104 µSv/h (LO1), with a mean of of 1.438 µSv/h. Non-aerated locations showed a slightly higher average value, with each location values ranging from 1.227 µSv/h (AH,PL,CL,SC) to 2.016 µSv/h (LO1, SC) and an average EDR value of 1.490 µSv/h, with both averages exceeding the global average of 0.133 µSv/h. Absorbed Dose Rates (ADR) were within safe limits. Aerated rooms recorded values between 0.61 and 2.10 nGy/h (mean: 1.44 nGy/h), while non-aerated rooms ranged from 1.22 to 2.01 nGy/h (mean: 1.49 nGy/h), all below the global average of 55 nGy/h. Annual Effective Dose Equivalent (AEDE) values were also below the recommended threshold of 1 mSv/y. Aerated areas ranged from 0.0030 to 0.0103 mSv/y (mean: 0.0070 mSv/y), and non-aerated areas from 0.0060 to 0.0099 mSv/y (mean: 0.0073). Excess Lifetime Cancer Risk (ELCR) values remained below the global average of 1.16 ×10⁻³, with aerated spaces ranging from 0.15 to 0.51 ×10⁻³ and non-aerated areas from 0.3008 to 0.4942 ×10⁻³. However, whole-body organ dose (D-organ) values exceeded the global average of 1 mSv/y. Aerated locations recorded 1.63 to 5.61 mSv/y (mean: 2.33 mSv/y), and non-aerated areas showed consistent values around 3.27 to 5.37 mSv/y. Conclusion: Despite the equivalent dose rate being above recommended limits, the AEDE, ELCR, and organ dose values remain within safe thresholds. This indicates that the elevated dose rate may result from temporary factors. Since overall exposure is low, the likelihood of long-term health risks, such as cancer, remains minimal in the school environment.